Main vegetables produced by seeds in the state of Rio de Janeiro (Research, Society and Development, 2022)
The present study aimed to identify the production of the 12 main vegetables propagated by seeds and seedlings in the state of Rio de Janeiro, in addition to researching the production of seeds in the state and the origin of seeds acquired by family farmers. This research was of an exploratory documentary character where the production data of the main vegetables propagated by seeds and cultivated in the state of Rio de Janeiro were analyzed, as well as the origin of the seeds used in these crops. The production of vegetables reproduced by seeds in the state of Rio de Janeiro is intense, generating jobs and moving the economy and is concentrated in the Center and Serrana regions, where most of the organic producers in RJ are also concentrated. This intense horticultural agricultural activity reveals the high dependence on seeds that are mostly produced outside the state of RJ. The study also points out that the large amount of administrative and technical requirements are revealed as an element that makes it difficult to produce seeds aimed at the broad commercial market, since they demand technical qualification so that they are met, both within the aspect of organic certification and within of the universe of laws and specific norms for seed production, where there are countless steps to be taken, from filling in electronic and physical forms for registration as a producer, own accreditation, technical responsible, going through the attendance of countless stages of seed production for that can ensure the physical, physiological, genetic and sanitary quality of the seeds, in accordance with maximum and minimum standards established by the Ministry of Agriculture, Livestock and Supply.